RBF neural network PID for Bilateral Servo Control System - Zhang Jingdong; Wen Guang; Wei Yongqiao; Yin Guofu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Tele-operated bilateral hydraulic servo system with master-slave robot at the core can be complex manipulated in uncertain or extreme environment (such as space, seabed, radicalization, battlefield, etc.). In this paper, a novel force feedback bilateral servo system is presented, based on analysis of bilateral servo system at home and abroad, which adopts tuning PID control algorithm with RBF neural network at the same time. From the simulation results, the novel force feedback bilateral servo system is presented to verify the effectiveness of the proposed control algorithm.The control briefness, fast response, strong robustness, good disturbance rejection capability and good adaptive capability can be obtained.It is also revealed from simulation results that the proposed control algorithm is valid for force feedback bilateral servo system and also provides the theoretical and experimental basis. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3269